The Violation of Politeness Maxim Principles Found in Skinnyindonesian24 Youtube Channel - Nisa, Elsara Khairun; Rustono, Rustono; Haryadi, Haryadi (Universitas Negeri Semarang, 2021)
The technological advancement in this 4.0 industrial era shifts conventional communication into social media communication. One of the preferred social media is YouTube by most Internet users in Indonesia. Thus, it makes YouTube free to use for every on so that many violations of politeness maxim principles. These violations made researchers eager to investigate with politeness theory of Leech. This research aims to find and identify the violated politeness maxim principle in the Skinnyindonesian24 YouTube channel. The researcher used a qualitative pragmatic approach with descriptive analysis. The data sources were from the conversational excerpt that might contain politeness maxim principal violation in YouTube’s Got Talent Part 1-3. Then, the research data sources were from the conversational excerpt in the Skinnyindonesian24 YouTube channel. The researchers collected the data with an observing technique. The advanced techniques were recording and notes. The data validity included data triangulation or data source triangulation and theoretical triangulation. The data analysis techniques of this research were normative and heuristic methods. The analyses showed some violations of tact, sympathy, approbation, generosity, agreement, modesty, opinion-reticence, feeling-reticence, the obligation of S to O, and the obligation of O to S maxims.